The Urgency of the Constitutional Court and Its Existence As an Institution Providing Justice - Ahlul Fiqri (JUSTICES: Journal of Law, 2023)
The Constitutional Court as an institution guarding the constitution has been able to carry out the mandate given to it, namely as an institution that protects the constitutional rights of every citizen. the mandate imposed on the Constitutional Court as a nature of court decisions contains the rights that will be owned by justice seekers. Therefore, the establishment of the Constitutional Court apart from being a supervisor and protector of the 1945 Constitution also serves as an institution that can provide legal guarantees for every legal product that is produced. However, as a judicial institution which is considered to be still young, there are many things that need to be studied further in this Constitutional Court, especially those related to urgency and existence in society. Because basically every judicial institution needs to formulate regulations that can be accepted by society and can protect their rights.